The Impact of Digital Economy on Residents' Health: Based on the Perspective of Population Ageing - You, Zhi-Ting; Zhong, Min; Gao, Qing; Wei, Hong-Xiang; Zeng, Xi-Hao (Frontiers in Public Health, 2021)
This paper uses panel data from inland provinces of China to perform a fixed effect regression and finds that the development of the digital economy has a significant promotional effect on the health of residents. Then, the population ageing rate is further used as a threshold variable for a threshold regression, and the relationship between the development of the digital economy and the health of residents from the perspective of ageing is discussed. The empirical results show that the ageing of the population will reduce the role of the digital economy in promoting residents' health. There is a non-linear single threshold effect between the development of the digital economy and residents' health indicators. In areas of China with a better developed digital economy, when the ageing rate exceeds the threshold, the positive impact of the development of the digital economy on population health has increased compared with the population ageing below the threshold. These asymmetric developments are closely related to economic development, historical and cultural factors, and policies formulated by the government. Therefore, as the digital economy continues to advance, the government should also provide health services fairly and efficiently, and formulate effective Internet assistance policies for the elderly so that the development of the digital economy can more comprehensively promote the health of residents of all ages.